Semipermanent Copper Nanowire Network with an Oxidation-Proof Encapsulation Layer - Hong, Insic; Roh, Yeonwook; Koh, Je Sung; Na, Seonyeob; Kim, Taewi; Lee, Eunhan; An, Hyeongi; Kwon, Jinhyeong; Yeo, Junyeob; Hong, Sukjoon; Lee, Kyu Tae; Kang, Daeshik; et al. (Advanced Materials Technologies, 2019)
Copper nanowires (Cu NWs) have gained attention as an alternative to noble metal nanowires due to their affordable price, but their susceptibility to rapid oxidization in ambient conditions has remained a critical limitation for their practical usage. Many studies have been conducted to address this disadvantage but have been successful only in terms of oxidation prevention at certain temperatures, leaving the matter of oxidation at high temperatures unresolved. In this article, a simple encapsulation structure made of a polyimide and SiOx thin film is presented that effectively prevents the penetration of oxygen and moisture into the Cu NW network. This structure, furthermore, boasts excellent stability at high temperature (≈350 °C) and in underwater, acidic chemical, and abrasive conditions.
Keywords: Affordable prices; Ambient conditions; Copper nanowires; Encapsulation layer; High temperature; Metal nanowire; Micro-heaters; Oxidation prevention; copper nanowires; CuPSP structures; flexible microheaters; oxidation